2020
DOI: 10.1002/gj.3787
|View full text |Cite
|
Sign up to set email alerts
|

A new Carboniferous–Permian intra‐oceanic subduction system in the North Tianshan (NW China): Implications for multiple accretionary tectonics of the southern Altaids

Abstract: The North Tianshan in NW China is a key to understanding the accretionary history of the southern Altaids. However, the tectonic setting of the North Tianshan in the Carboniferous‐Permian is debatable, and its amalgamation history is ambiguous. We report new data on the field relations, geochronology and geochemistry of Carboniferous–Jurassic volcanic rocks and sedimentary rocks from the Shichang area in order to constrain the late Palaeozoic–Early Mesozoic tectonic evolution of the North Tianshan. New LA‐ICP‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
(162 reference statements)
1
12
0
Order By: Relevance
“…Ao et al (2021) identified the youngest matrix at 234 Ma in the Kanguer mélange, suggesting continuous northward subduction of the North Tianshan oceanic lithosphere in the late Triassic. By doing provenance exchange study, Abuduxun et al (2021), Song et al (2021), Bai et al (2020), and Chen et al (2020) suggested that there was only provenance exchange at the early to late Triassic in the South Tianshan orogen, Alxa block, and North Tianshan orogen, respectively, indicating closure of the corresponding oceans in the Triassic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ao et al (2021) identified the youngest matrix at 234 Ma in the Kanguer mélange, suggesting continuous northward subduction of the North Tianshan oceanic lithosphere in the late Triassic. By doing provenance exchange study, Abuduxun et al (2021), Song et al (2021), Bai et al (2020), and Chen et al (2020) suggested that there was only provenance exchange at the early to late Triassic in the South Tianshan orogen, Alxa block, and North Tianshan orogen, respectively, indicating closure of the corresponding oceans in the Triassic.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that these rocks were the products of backarc rifting of the Harlik‐Dananhu composite arc, but this conclusion requires re‐evaluation (Li et al, in press). Both southward and northward subduction of oceanic basins (various names were used, including the Kelameili Ocean) were proposed to be responsible for the construction of the Bogda arc or intra‐arc basin (Bai et al, 2020; Chen et al, 2013; Xie et al, 2016; Zhang et al, 2017).…”
Section: Regional Geology and Tectonic Backgroundmentioning
confidence: 99%
“…Bai et al (, this issue) present new data on the field relations, geochronology and geochemistry of Carboniferous–Jurassic volcanic rocks and sedimentary rocks from the Shichang area. The detrital zircon data suggest the presence of a so‐far unrecognized intra‐oceanic arc during the Late Carboniferous to Permian in the southern Altaids, most likely formed by processes of multiple subduction–accretion and convergence similar to that in the on‐going southwest Pacific.…”
Section: Western Altaidsmentioning
confidence: 99%
“…It contains many accretionary prisms and is the key area to reconstruct the architecture of the Altaids because it represents the terminal suturing between the Tarim Craton and the Northern Ili Arc (NIA; Abuduxun et al., 2021). The geology and tectonic history of the Tianshan Orogen has been primarily investigated in the South Tianshan accretionary complex (STAC; e.g., Alexeiev et al., 2015; C. M. Chen et al., 1999; Gao & Klemd, 2003; B. F. Han et al., 2011; Jiang et al., 2014; Safonova, Biske, et al., 2016; Sang et al., 2020; B. Wang et al., 2011; G. X. Yang et al., 2017), located between the Tarim Craton and the Issyk Kul‐Central Tianshan Arc (CTA), and the North Tianshan Accretionary Complex (NTAC; e.g., Bai et al., 2020; Feng et al., 2018; M. Wang, Zhang, Pei, et al., 2018; Xu et al., 2005; G. X. Yang et al., 2018; Zheng et al., 2019) adjacent to the Junggar arcs and the NIA (Figure 1). Relatively less attention has been paid to the relationship between the Issyk Kul‐CTA and the NIA separated by the Terskey‐North Nalati Suture Zone which may connect to the Nikolaev line in its western branch (Gao et al., 2015; G. Q.…”
Section: Introductionmentioning
confidence: 99%
“…, located between the Tarim Craton and the Issyk Kul-Central Tianshan Arc (CTA), and the North Tianshan Accretionary Complex (NTAC; e.g., Bai et al, 2020;Feng et al, 2018;M. Wang, Zhang, Pei, et al, 2018;Xu et al, 2005; G. X.…”
mentioning
confidence: 99%